Microcosm investigation of growth and phytoremediation potential of Azolla japonica along nitrogen gradients. Issue 10 (3rd October 2017) - Park, Hun; Song, Uhram
ABSTRACT: Although Azolla species are among the most promising plants for use in phytoremediation, more studies on their growth and nitrogen (N) uptake along the N gradients of growing media are required. In this study, N concentration-dependent growth in growing media and phosphorus (P) and N accumulation by Azolla japonica were studied by estimating direct N uptake from media by molybdenum-iron proteins. The doubling time of A. japonica was less than a week, regardless of the N concentration (0, 5, and 25 mg N/L) present in the growth media, indicating that this plant is suitable for remediation. Plants showed a high uptake of P, probably via plant-bacteria symbiosis, indicating their potential for effective P remediation. A. japonica also showed more than 4% N content regardless of the treatment and accumulated more than 40 mg of N per microcosm in 3 weeks. iron and molybdenum levels in plants were strongly associated with N fixation, and N uptake from media was estimated to be more than 25 mg per microcosm in 3 weeks, indicating that A. japonica has N remediation potential. As A. japonica is a rapidly growing plant, capable of efficient P and N remediation, it has great potential for use in phytoremediation of nutrient-enriched waters such as agricultural or urban wastewater and eutrophicated aquatic ecosystems.